Mitigating soil salinity–alkalinity and reshaping bacterial community to improve soil organic carbon sequestration in the Hetao Irrigation District: a combined approach of organic ameliorant and microbial agents - Yu, Ru; Zhang, Xia; Zhou, Jie; Wang, Weini; Song, Jiashen; Chang, Fangdi; Wang, Jing; Li, Haoruo; Li, Xiaobin; Li, Haigang; Zhang, Hongyuan (Frontiers in Plant Science, 2026)
Microbial agents promote the decomposition and the transformation of organic materials, enhancing the utilization of organic ameliorants in saline–alkali soil. However, the effects of the combination of organic ameliorants and microbial agents on the soil organic carbon (SOC) pool and the underlying regulatory mechanisms are poorly understood. Consequently, a 2-year field experiment was conducted in 2022–2023 to investigate changes in the SOC fractions and pools, as well as the regulatory pathways under different organic ameliorants: no organic ameliorants (CK), sole organic ameliorants (O), and organic ameliorants combined with microbial agents (O+M). O+M was superior to O treatment in improving the soil saline–alkali and nutrient conditions, alleviating the microbial carbon (C) and phosphorus (P) limitation and increasing the bacterial diversity and richness in saline–alkali soil. Community analysis revealed that O+M preferentially enriched the K-strategists (Actinobacteriota, +16%; Acidobacteriota, +6%), increasing the bacterial K/r ratio by 9% compared with O treatment. Partial least squares path modeling (PLS-PM) identified distinct SOC accrual pathways: the O and O+M treatments directly enhanced SOC, the O treatment increased the particulate organic carbon (POC) via bacterial diversity-mediated nutrient cycling, whereas the O+M treatment promoted POC through K/r ratio shifts and the mineral-associated organic carbon (MAOC) via soil content and pH modulation. Ultimately, O+M achieved the highest SOC (8.26 g kg−1, +34% vs. CK), with MAOC contributing 32% of the total increment, 61% higher than that of O treatment. This mechanistic study elucidates how microbial–metabolic coordination and abiotic stabilization jointly regulate the persistence of SOC in degraded soils, providing a synergistic bioremediation strategy for saline–alkali ecosystems.